Reciting Poetry in Contemporary EFL Instruction - Josifović Elezović, Sanja (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper analyses the effects of reciting various poetic texts in a foreign language instruction at the advanced level, in order to improve linguistic, cultural, and personal competences of English language students. Contemporary foreign language teaching methodology is reviewed briefly, and the possibilities and consequences of using different poetic styles are considered, in the ways that successfully integrate foreign and native language, literature and culture, intensive and extensive reading in a foreign language. Final year students of English language and literature at the Faculty of Philology in Banja Luka participate in a project of reciting world poetry in English in front of an audience, within the compulsory subject Contemporary English Language 7. In this case study from the academic 2016/2017, the perceptions of 25 students of English language and literature and the observation notes of their professor, project leader, are critically analysed, after their participation in the recitation project. The aim of the study is to gain a better insight into the effectiveness of reciting poetry in a foreign language by university students, and in other contexts in which a foreign language is learned. İn this qualitative research, the method of data interpretation is content analysis, and the data collection methods are observation and survey. The research instrument is a questionnaire with open-ended questions. The results show that by practicing reciting in a foreign language for a public appearance in front of colleagues and an audience, students can significantly improve their personal, linguistic, cultural, and professional competencies.
Keywords: English as a foreign language; foreign language instruction; literature; poetry; project; recitation; students